2020
DOI: 10.1016/j.celrep.2020.107973
|View full text |Cite
|
Sign up to set email alerts
|

GSK3 Inhibits Macropinocytosis and Lysosomal Activity through the Wnt Destruction Complex Machinery

Abstract: Highlights d GSK3 and Axin1 normally repress macropinocytosis in basal cellular conditions d GSK3 inhibition or Axin1 mutation triggers macropinocytosis and metabolite changes d Macropinocytosis induces acidification and catabolic activity of lysosomes d Lysosomal activation by Wnt signaling is independent of new protein synthesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 59 publications
(101 reference statements)
3
108
0
Order By: Relevance
“…The strong link between the Wnt and ALP pathways we observed suggests the existence of a bi-directional feedback loop, so that alterations in one pathway may affect the other. This idea is in line with other reports on the ability of the endo-lysosomal system to modulate Wnt signaling and in turn, the Wnt pathway regulating the lysosomal compartment [35,61,63,[72][73][74][75]. Albrecht et al reported an increase in both endocytosis and the lysosomal degradation of extracellular proteins within minutes of the addition of Wnt3a in NIH-3T3 fibroblasts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The strong link between the Wnt and ALP pathways we observed suggests the existence of a bi-directional feedback loop, so that alterations in one pathway may affect the other. This idea is in line with other reports on the ability of the endo-lysosomal system to modulate Wnt signaling and in turn, the Wnt pathway regulating the lysosomal compartment [35,61,63,[72][73][74][75]. Albrecht et al reported an increase in both endocytosis and the lysosomal degradation of extracellular proteins within minutes of the addition of Wnt3a in NIH-3T3 fibroblasts.…”
Section: Discussionsupporting
confidence: 89%
“…Albrecht et al reported an increase in both endocytosis and the lysosomal degradation of extracellular proteins within minutes of the addition of Wnt3a in NIH-3T3 fibroblasts. Additionally, Wnt3a treatment or inhibition of GSK3β in HeLa and HCC Alexander cells increased Lysotracker staining, and Cathepsin D and GCase activity [75]. A neuroprotective effect of Wnt ligands in vivo has also been reported [76][77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, an important function of Wnt signaling in this context seems to be a constant down-regulation of a sub-pool of Wnt-controlled basal GSK3β activity. It is interesting that fine-tuned regulation of Wnt associated GSK3β activity seems not only be important for mitotic regulation, but also, for example, for macropinocytosis and metabolite changes as demonstrated recently (38). Importantly, down-regulation of basal GSK3β required for proper mitosis is mediated by basal Wnt signaling that requires ongoing secretion of Wnt ligands.…”
Section: Discussionmentioning
confidence: 92%
“…These optimized protocols, applied in different cell types and pathophysiologic contexts, provide useful tools to study lysosome function in cultured living cells. For complete details on the use and execution of this protocol, please refer to Albrecht et al. (2020) .…”
mentioning
confidence: 99%
“…For complete details on the use and execution of this protocol, please refer to Albrecht et al. (2020) .…”
mentioning
confidence: 99%